TRANSFORMASI PENDIDIKAN ISLAM HOLISTIK: STUDI KASUS PENDIDIKAN KADER ULAMA MUHAMMADIYAH DI UNIVERSITAS MUHAMMADIYAH PALANGKARAYA - Hunainah, Hunainah; Lastaria, Lastaria; Ramdhani, M. Tri; Usop, Dwi Sari (Jurnal Hadratul Madaniyah, 2024)
Islamic education continues to transform over time by self-improvement. Holistic Islamic education offers students the ability to adapt to changing times while still emphasizing religion as the main axis. Muhammadiyah Ulama Cadre Education (PKUM) is one of the bases for the cadre formation of Muhammadiyah ulama in Central Kalimantan. Although holistic Islamic education is not a new concept, its implementation needs to be renewed and adapted to the environment. This article is part of descriptive qualitative research, aiming to describe the transformation of holistic Islamic education occurring in the PKUM (Muhammadiyah Ulama Cadre Education) institution at Muhammadiyah University of Palangkaraya, Central Kalimantan. The research results show that the transformation of holistic Islamic education in PKUM-UMPR has strived to fill the cognitive, affective, and psychomotor students, centered on tauhid. PKUM's efforts to transform holistic Islamic education include academic education in dormitories and on-campus within the Faculty of Islamic Studies, as well as various forms of tiered coaching and cadre formation, so that the cadres can lead and become ulama when they return to their respective PDMs (Muhammadiyah Regional Leaders).